Frequency of gestational malaria and maternal–neonatal outcomes, in Northwestern Colombia 2009–2020 (2022)
ABSTRACT: Research on Gestational Malaria (GM) is scarce in America’s. In the few available studies in Colombia, the analysis of immunological or parasitological aspects predominates, with few analyzes of epidemiological aspects. The objectives were to determine the frequency of GM and submicroscopic infections (positive with PCR and negative with thick blood smears), to identify obstetric and malaria history associated with GM, and to describe maternal and neonatal outcomes associated with GM, in northwestern Colombia. A retrospective study with records of 825 pregnant women was conducted. qPCR and thick blood smear were performed. Frequencies were determined with 95% confdence intervals. Comparisons were made with the Chi-square test, Mann–Whitney U test, and prevalence ratios adjusted in a log-binomial model. The frequency of GM was 35.8% (95% CI 32.4–39.1) of submicroscopic infection was 16.2% (95% CI 13.7–18.8). According to the multivariable model, the subgroups with the highest frequency of GM were pregnant women without healthcare coverage (32.3%), in the third trimester of pregnancy (30.5%), nulliparous (35.6%), and with a previous diagnosis of malaria in the current pregnancy (64.0%). GM was associated with more frequency of gestational anemia, infection in neonates, and lower birth weight. The results indicate in a precise and direct way that malaria control in this northwestern region of Colombia is far from adequate, which is even more serious considering the afectations for the mother and the neonate.